An Efficient Approach Implementation to Image Compression and Encryption - Asst. Prof. Dr.Baheja K.Shukur; Swasan Hadi; W. Al-Hameed (Genius Journals, 2022)
The intent of image compression is to cut down the redundancy of the image and to store or transmit data in an effective form. Also, the encryption is considered one of the important fields in the computer industry which is specialized in the Information Security transmission. Encryption, the process which helps in such secure transmission, prevents hackers from accessing the information. Decryption assists to recover the original information. This paper contains an approach to applying image compression with encryption using the secret key. The major goal of such method is to reduce the RGB image quantity as much as possible using DCT transform, and quantized the resulted image using Rounded to nearest integer, Default Quantization Tables (chrominance , Luminance), Simple Quantization Tables, and default table. after quantization process the run-length encoding algorithm RLE is used. i.e. the DCT transform applies for each band of RGB image and three methods of quantization applied to the resulted coefficients then the RLE compression method used. However alone compression is not sufficient as it has an open access, anybody can access it. So if it is desired that it can be accessible only by authorized person it should be encrypted as well. In the encryption process divided the resulted RLE matrix for each band of the RGB image into the odd and even position and encrypted them using a key generator, which consist of three registers each one of 32 bit length and connected with each other using strong non- linear function, To increase the security of this system, the encryption process did not sequentially . The receiver decrypts the encryption file then apply the RLE decoding and the dequantization process. Finally, the inverse of the DCT algorithm made. To assess our system number of measurements used such as histogram, correlation, and compression ratio C.R between the compression and retrieved images for each method of the quantization to show the strength of this system. This system implemented using visual basic 6.0
Keywords: DCT; Quantization; RLE; Encryption